Effect of expiry date communication on acceptability and waste of fresh-cut lettuce during storage at different temperatures. (February 2019) - Alongi, Marilisa; Sillani, Sandro; Lagazio, Corrado; Manzocco, Lara
Abstract: The effect of expiry date communication on acceptability and wasting risk of fresh-cut lettuce was investigated. Fresh-cut lettuce was packed in plastic pouches reporting or not the expiry date on the label and stored at recommended (8 °C) or abuse temperature (12 °C) for increasing time up to 21 days. Lettuce was assessed during storage for colour, total viable count, consumer rejection and wasting risk. Independently on storage temperature, the presence of the expiry date caused an increase of wasting risk. When lettuce was stored at 8 °C, about 4% packages were estimated to be wasted within the expiry date (7 days). Even a lower amount of waste was estimated when expiry date was not reported. Within 7 days of storage at 12 °C, 12% of the packages without expiry date was estimated to be wasted. This percentage increased to 27% when the expiry date was printed on the lettuce label. Results emphasise the dramatic effect of the presence of the expiry date on the consumer decision to waste food. Graphical abstract: Unlabelled Image Highlights: Domestic waste of fresh-cut salad was estimated by the wasting risk methodology. Independently on storage temperature, expiry date communication increased salad waste. At 8 °C expiry date communication increased salad waste from 1 to 4%. At 12 °C salad waste increased from 12 to 27% when the expiry date was communicated.